Evaluation of anti-diabetic activity of Justicia adhatoda (Linn.) Leaves in diabetic wistar rats - Roshan Kumar Mehta; Rupkala Thapa; Mukesh Kumar Chaudhary (Journal of Universal College of Medical Sciences, 2023)
INTRODUCTION Diabetes mellitus is deﬁned as the increase in blood glucose level resulting from defects in insulin secretion, insulin action, or both. The present study was conducted to evaluate anti-diabetic activity of Justicia adhatoda (Linn.) leaves extract in diabetic Wistar rats. Justicia adhatoda, commonly known as vasaka is rich in phytochemicals like alkaloids, saponins, steroids, ﬂavonoids and glycosides. It is used in asthma, jaundice, wound healing, typhus fever, cough, chronic bronchitis and inﬂamma- tory swellings treatment. MATERIAL AND METHODS The extract was obtained by maceration process with the use of methanol as solvent. 30 Wistar rats of 150-250 gm were used taken as study animal. Diabetes was induced by single intraperitoneal injection of Alloxan 150 mg/kg body weight. The methan- olic extract of low dose (50 mg/kg) and high dose (100 mg/kg) were given orally for anti-diabetic activity. The standard drug glimepiride 0.5 mg/kg body weight was used. RESULTS The extract treated 50mg/kg and 100mg/kg showed signiﬁcant p<0.01 reduction in blood glucose level while the standard 0.5 mg/kg showed less signiﬁcant p<0.05. The standard and extract showed less signiﬁcant p<0.05 body weight recovery in compar- ison to negative control group. The extract 50 mg/kg, 100 mg/kg and standard showed signiﬁcant p<0.01 improvement in food intake when compared to negative control group. The extract 100 mg/kg treatment showed signiﬁcant p<0.01, highly signiﬁcant p<0.001 improvement in water intake on 1st, 2nd and 3rd week respectively when compared to negative control group. CONCLUSION The present study concludes that the extract possesses potent and signiﬁcant anti-diabetic activity of Justicia adhatoda leaves.